Inception - Carter, David R., 1945- (Constellations (Leighton Buzzard, England), 2019)
Christopher Nolan's Inception (2010) is a difficult film to categorize. It partakes of various genres, blurring the distinctions between them. Yes, it is science fiction but it does not contain many of the ingredients associated with that genre. It can also be identified as a kind of heist film, and there are shades of film noir as well, not only because of the heist motifs but also due to its character types. It can also be described as psychological thriller, telling the story of one man's attempt to flee his past and regain access to his family, of his coming to terms with the death of his.